GAL11 protein, an auxiliary transcription activator for genes encoding galactose-metabolizing enzymes in Saccharomyces cerevisiae. - Suzuki, Y (1988)
Normal function of the GAL11 gene is required for maximum production of the enzymes encoded by GAL1, GAL7, and GAL10 (collectively termed GAL1,7,10) in Saccharomyces cerevisiae. Strains bearing a gal11 mutation synthesize these enzymes at 10 to 30% of the wild-type level in the induced state. In a DNA-RNA hybridization experiment, the gal11 effect was shown to be exerted at the transcription level. Yeast cells bearing the gal11 mutation were shown to grow on glycerol plus lactate more slowly than the wild type. We isolated recombinant plasmids carrying the GAL11 gene by complementation of the gal11 mutation. When the GAL11 locus was disrupted by insertion of the URA3 gene, the resulting yeast cells (gal11::URA3) exhibited phenotypes almost identical to those of the gal11 strains, with respect to both galactose utilization and growth on nonfermentable carbon sources. Deficiency of Gal4, the major transcription activator for GAL1,7,10, was epistatic over the gal11 defect. The Gal11 deficiency lowered the expression of GAL2 but not that of MEL1 or GAL80; expression of these genes is also known to be dependent on GAL4 function. We determined the nucleotide sequence of GAL11, which is predicted to encode a 107-kilodalton protein with stretches of polyglutamine and poly(glutamine-alanine). An alpha-helix-beta-turn-alpha-helix structure was found in a distal part of the predicted amino acid sequence. A possible role of the GAL11 product in the regulation of galactose-inducible genes is discussed.